Radiation of a monopole antenna in a reverberation chamber - Xiao, Xiao (2009)
The Reverberation Chamber (RC) has been used for about a decade as a statistical electromagnetic (EM) field generator. It has for many years found application in the EMC (electromagnetic compatibility) area for EMC measurements. This project report is mainly about the radiation of the fundamental monopole antennas inside a reverberation chamber. The first half of the report introduces the basic knowledge of the reverberation chamber and the antenna parameters. Theoretical simulation results of a simple monopole antenna in free space are presented to provide a visual impression of those parameters. A brief literature review of this studied area will also be presented, especially for the application of the reverberation chamber. Simulation results are demonstrated in the second half of the report. Two kinds of chambers are used. One is a cubic of 14.4 cm x 14.4 cm x 14.4 cm, the other one is cuboids of size 50 cm x 30 cm x 20 cm. Each chamber was first fed by one 5 cm long monopole at the bottom center inside the chamber, and then another monopole was allocated along the direction perpendicular to the original one; at last the third monopole was inserted into the chamber in the direction that is normal to the plane formed by the previous two monopoles, thus the three antennas are orthogonal. Practically only cuboids chambers are used, and the validity is shown by the simulations results, since the second chamber gives a more correct result. Comparisons between each case are presented. Changes in electrical field and the return loss as well as the input impendence are shown. It is found that boundary conditions are changed due to the insertion of monopoles and there are more cut-off frequencies excited under the multi-monopole environment. Further study can be done by changing the length of the monopoles as well as changing their positions in the cuboids chamber.